To divide 4x - 1 by 12x + 7, we need to perform polynomial long division.
Step 1: Divide the first term of the numerator by the first term of the denominator.
4x / 12x = 1/3
Step 2: Multiply the result by the entire denominator.
(1/3)(12x + 7) = 4x + 7/3
Step 3: Subtract the result from the numerator.
4x - (4x + 7/3) = -7/3
Step 4: Bring down the next term from the numerator.
-7/3 + 1 = -4/3
Since we can no longer divide the term -4/3 by 12x + 7, the final result after dividing 4x - 1 by 12x + 7 is:
1/3 - 4/3(12x + 7) + (-4/3)
Divide.
4x-1/12x+7
1 answer